Description of Polymer and Composite Hardening During Tensile Tests - Nowak, M. (Engineering Transactions, 1992)
Tensile stress-strain curves of plastics and polymer composites are prepared and analyzed, the effects of temperature, water diffusion, heat treatment and notches being taken into account. The conditions are determined under which the tensile stress-strain diagrams may be described by rectilinear segments (schematization) in the entire loading range. The analysis was carried out at the set of 465 diagrams. The attempt was made to furnish a physical interpretation of the hardening effect of three types of materiaIs: Polyamide 6 (Tarnamide T-27 and Block Tarnamide) and Polyamide 6 reinforced by glass microballs (Itamide 58-D). Polyesther-ether elastomers (KPEE) were also considered in the analysis.